Inferring deep ocean tidal energy dissipation from the global high‐resolution data‐assimilative HAMTIDE model. Issue 7 (28th July 2014) - Taguchi, E.; Stammer, D.; Zahel, W.
Abstract Energy dissipation rates of eight major semidiurnal and diurnal tidal constituents are inferred using a barotropic data assimilative tide model with 7.5' spatial resolution. Dynamical residuals and dynamical residual power, estimated through the assimilation procedure as a correction for model uncertainties, constitute an essential contribution to deep‐ocean and shallow‐seas dissipation rates. Resulting total dissipation rates amount to 3.54 TW, of which 2.44 TW (69%) are accounted for by the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh11p2c325" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M2</alternatives> component alone. Concentrating on the deep ocean (> 1000 m water depth), the dissipation by all eight constituents amounts to 1.42 TW, and 0.93 TW just for the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh11p2c35t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M2</alternatives> component. These results are higher by 19% and 38% than dissipation rates estimated by Egbert and Ray (2003), respectively. Of the globally dissipated <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh11p2c2ww" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2.44TWM2</alternatives> energy, 1.24 TW are estimated to arise from bottom drag and eddy turbulence, 1.20 TW from residual power. For just the deep ocean, respective numbers amount to 0.10 TW for bottom drag and eddy turbulence, 1.07 TW for barotropic‐to‐baroclinic energy conversion due to the internal wave drag. Interpreting negative residual power −0.24 TW as a potential tidal energy source, a net surface‐to‐internal tide <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh11p2c31m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M2</alternatives> energy conversion would amount to 0.83 TW.